The use of cloud technology in Corporate Information Systems - Talibov, Rufat; Jafarov, Zafar (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
For automation industry, Information Technology (IT) is an essential production factor, but also a major expense post. Because cloud computing promises to deliver IT services more flexibly and cost-efficiently, it for automation industry prospectively. However, given the high degree of regulation, concerns regarding security and compliance requirements arise. In this work, provide a theoretical analysis of security problems in the context of cloud computing. This analysis is complemented by the initial results of an ongoing case study concerning the practical relevance of these problems in the industry. The analysis confirms that security issues pose notable obstacles for the adoption of cloud computing in practice, but also points to appropriate countermeasures